2015
DOI: 10.15275/rusomj.2015.0301
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between individual identities and the mental health among students

Abstract: Background-Nowadays, the relationship between Individual Identities and the mental health is as one the most important matter in developing countries. Aim-The aim of this study was to investigate the relationship of Individual Identity and the mental health of the students. Material and Methods-The subjects of this study were 1293 undergraduates (age: 22±4 (mean±SD)) studying in the fourth region of Islamic Azad University, Iran in the academic year of 2012-2013. They were selected through random sampling. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies were excluded if they presented insufficient data; if they were mere reviews; or if they were not epidemiologic studies. 8,[20][21][22][23] Statistical Analysis Articles were combined based on the sample size, means and SDs. Because of the low number of articles used and because these articles had been published in prestigious journals, quality criteria were not included in the analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies were excluded if they presented insufficient data; if they were mere reviews; or if they were not epidemiologic studies. 8,[20][21][22][23] Statistical Analysis Articles were combined based on the sample size, means and SDs. Because of the low number of articles used and because these articles had been published in prestigious journals, quality criteria were not included in the analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…The purpose of studying these statuses is to attempt to determine one's commitment to identity and their tendency to explore other identity-related experiences through "observed associated personality characteristics, patterns of interpersonal relations, and developmental forms of movement over time (Kroger, 2017). After the four configurations were reviewed, it has been concluded that one is more likely to suffer from mental disorders if in foreclosure, moratorium, or diffusion identity (Sharifi, 2015). Therefore, the only status that does not have a likelihood of mental illness is identity achievement, which is when the individual has both committed to identity as well as explored and expanded the character that they have chosen to display.…”
Section: Introductionmentioning
confidence: 99%
“…Even when one has attained identity achievement, identity regression always exists to a degree and has the opportunity to arise again. Some adolescents may find themselves unable to fully attain their identity, which can lead to various problems in their current and future lives (Sharifi, 2015). Since identity is the foundation of all values and is a considerable factor in all decisions a teenager makes, it can create many complications for them as they continue to age and face more complicated issues.…”
Section: Introductionmentioning
confidence: 99%